Analisis Pengembangan Fitur pada Media Pembelajaran ILMI Menggunakan Metode UEQ: Analysis of Feature Development in ILMI Learning Media Using the UEQ Method - Yohan Bakhtiar (Politeknik Negeri Malang, 2026)
The Interactive Learning Media of Inventory (ILMI) is a learning platform equipped with an assistant character to support the Introduction to Accounting course. The latest development of ILMI includes additional features such as exercises and practice questions to enhance learning effectiveness. An evaluation was conducted using the User Experience Questionnaire (UEQ) method to assess the impact of these new features. The research stages consisted of literature review, instrument development, data collection, result analysis, and conclusion. The findings show that the enhanced version of ILMI achieved a score in the range of 5.6–6.1, which is higher compared to the previous version with a score of 3.8–4.2. These results indicate that the added features successfully improved both user experience and the effectiveness of the learning media.